The Byzantine icon as an expression of the composition of the “Beautiful” with the “Sublime” - Terezis, Christos (Dia-noesis: A Journal of Philosophy, 2024)
In this article I attempt to discuss the encounter between Christian Theology and the philosophical branch of Aesthetics. As a basis I have the icons of the Byzantine tradition, which also express the ecclesiastical way of its culture. First of all, I refer to what is defined as the aesthetic interpretation of a work of art and then to how its process receives theological characteristics in the style and approach of Byzantine icons. Next, I present the main characteristics of the artistic-aesthetic categories of the “Beautiful” and the “Sublime” and I undertake the responsibility to show how they function in Byzantine icons, with the former mainly expressing beauty and the latter mainly the intensive direction towards the divine. I also attempt to present some of the conditions by which a Byzantine icon is created, so that it captures, in an artistically and aesthetically remarkable way, holiness and is interwoven with the devotional life of the Christian church. In this perspective, I emphasize that the Byzantine icon reveals: a) how Jesus Christ, as an expression of manhood, fully realizes the immanence of the Holy Trinity and b) how his example is realized as a feat and as an expression of “image of God” from the saints. As an example of the above, I bring the icon “The Vaiophoros” of the Stavronikita Monastery of Mount Athos, which is the work of Theophanes from Crete. I choose it to show how the main directions of the Byzantine style regarding the composition of the “Beautiful” with the “Sublime” also meet during the post-Byzantine period.